Magnetic Characterization of Ca-Hexaferrites Using Hysteresis Technique - Khobaragade, C.L.; Soni, S.V.; Akant, A.K.; Khatarkar, R.K.; Wagdhare, N.A.; Khobragade, C.B.; Rewatkar, K.G. (Asian Journal of Chemistry, 2012)
In the present investigation the samples with chemical composition Ca1-x-y(CoTi)0.5MnxZnyFe11O19 with (x = y = 0-0.5) were synthesized using perfect stoichiometric proportions of reacting oxides by standard ceramic technique. Hexagonal magnetoplumbite (M) structure having unit cell dimensions 'a' and 'c' which varies in the range between 5-6 Å and 21-23 Å with space group P63/mmc (No. 194). The coercivity, retentivity, saturation magnetization and magnetic moment increases successively with increase in Mn-Zn concentration by changing magnetic field at 300 K. The room temperature resistivity increases in the range of 106 W cm. The grain size of the studied compounds varies in the range 0.29-0.79 mm (i.e., 290-790 nm). The superexchange interaction, Me-O-Me is responsible for magnetic behavoiur and found to increase with the increase of the Mn-Zn concentration in Ca-M compounds. It is found that there is a variation in hysteresis loops with change in magnetic field. The neutron diffraction and NMR studies also reveals that Co3+ ions are mainly distributed within 4fiv and 12 k sites of the studied compound.